Management and Outcome of Ewing Sarcoma of the Head and Neck. Issue 4 (24th December 2015) - Grevener, Knut; Haveman, Lianne M.; Ranft, Andreas; van den Berg, Henk; Jung, Susanne; Ladenstein, Ruth; Klco‐Brosius, Stephanie; Juergens, Heribert; Merks, J Hans M.; Dirksen, Uta
Abstract : Background: Ewing sarcoma (EWS) of the head and neck is rare. Multimodal treatment consists of chemotherapy and local treatment; however, local treatment for EWS of the head and neck is challenging. The first objective was to describe local treatment administered to the patients with localized EWS of the head and neck according to the EURO‐E.W.I.N.G.99‐trial, and to assess the impact on survival. The second objective was to systematically review the scientific literature available for this topic. Procedure: Fifty‐one patients were included. Local control consisted of surgery and/or radiotherapy (RT). Event‐free survival (EFS) and overall survival (OS) were determined. Outcome was analyzed by comparing local treatment approaches. A Medline search was performed for EWS of the head and neck. Results: Eighty‐six percent of patients had localized disease. Most common primary sites included the skull (45%), maxilla (14%), and mandible (12%). Three‐year EFS was 74% and 3‐year OS was 87% for patients with localized disease. EFS was 40% for patients >15 years compared to 81% for patients <15 years. Local control consisted of surgery (S; 33%), RT (18%), or S + RT (45%). Related 3‐year EFS was 81% (S), 80% (RT), and 72% (S + RT); 3‐year OS was 80%, 76%, and 81%, respectively. Conclusions: In patients with EWS of the head and neck, age, and stage are important prognostic factors. Although not statistically significant, large tumor volume seems to be a negative prognostic factor. No difference in EFS and OS could be found when comparing patients treated with surgery, RT, or combined surgery and RT.